THE PROBLEMATIC OF INTERPRETING RELIGIOUS TEXTS IN THE PHILOSOPHY OF JÜRGEN HABERMAS AND ITS REPRESENTATIONS IN THE PUBLIC SPHERE - Latroche Ahmed (International Journal of Innovative Technologies in Social Science, 2025)
This paper explores the philosophical approach of Jürgen Habermas to the interpretation of religious texts, focusing on how communicative rationality can serve as a tool for meaningful dialogue within the modern public sphere. It addresses the epistemological and hermeneutic challenges posed by the reinterpretation of religious traditions in contemporary societies, where secular and pluralistic values often clash with inherited religious meanings. On the basis of Habermas’s communicative action theory and his engagement with modern hermeneutics, this study examines how rational discourse can foster mutual understanding and uncover the deeper layers of meaning embedded in religious language. Particular attention is given to the distinction between discursive and nondiscursive validity claims, the role of language in shaping public reasoning, and the potential of interpretation as a means of cultural integration and ethical reflection. By connecting Habermas’s ideas with broader hermeneutic traditions and thinkers such as Mohammed Arkoun and Paul Ricœur, the paper highlights the critical function of interpretation in negotiating the boundaries between faith and reason, tradition and modernity. Ultimately, the study affirms that the rational reinterpretation of religious texts is essential to fostering inclusive dialogue and sustaining democratic coexistence in pluralistic societies.